An analysis of online education perception among faculty of sports sciences students following the February 6th Turkey earthquake - Haci Ali Cakici; Yilmaz Aksoy (ROL Spor Bilimleri Dergisi)
The purpose of this study is to examine the perception of online education from the perspective of students after the February 6th earthquake in Turkey. The study included 7 students from the Faculty of Sports Sciences at Ordu University. A semi-structured interview form consisting of 9 questions was prepared to determine the students' opinions regarding the online education approach after the February 6th earthquake. The data of the research were transferred to the Nvivo program and analyzed using a descriptive analysis method. The findings revealed differences between the approach to distance education after Covid-19 and the February 6th earthquake in Turkey, as well as the effectiveness of practical and theoretical lessons. Additionally, students' opinions about focusing on lessons and school after the earthquake disaster, attention diversion, and anxiety levels were identified. As a result of data analysis, it was concluded that face-to-face education would be more beneficial than online education. According to these results, while theoretical lessons could be conducted online, practical lessons should be held in a face-to-face format or in a more realistic environment. Furthermore, recommendations were made, including collaboration between the Higher Education Council and the Ministry of Youth and Sports, to enhance the effectiveness of practical lessons in the Faculty of Sports Sciences.